Exposure assessment to mycotoxins in a Portuguese fresh bread dough company by using a multi-biomarker approach - Viegas, Susana (2018)
Mycotoxins are toxic mold metabolites that can persist in environment long after the fungi species responsible for their production disappear. Critical workplace for mycotoxins presence has already been studied and nowadays it is possible to recognize that exposure to mycotoxins through inhalation occurs due to their presence in dust. This study aimed to assess occupational co-exposure to multiple mycotoxins in a fresh bread dough company, an occupational setting not studied until now. Occupational exposure assessment to mycotoxins was done using a LC-MS/MS urinary multi-biomarker approach. Twenty-one workers and nineteen individuals that were used as controls participated in the study. Workers/controls (spot-urine) and environment (settled dust) samples were collected and analyzed. Concerning workers group, DON-GlcA, and OTA were the most prevalent biomarkers (>LOD), 66% and 90.5%, respectively. In the control group, OTA was also one of the most detected (68%) followed by CIT (58%) and DON-GlcA (58%). DON was the mycotoxin measured in high amounts in the settled dust sample (58.2 ng/g). Both workers and controls are exposed to several mycotoxins simultaneously. The workers group, due to their high contact with flour dust, revealed a higher exposure to DON. Considering these results, risk management measures must be applied including specific and adequate health surveillance programs in order to avoid exposure and consequently the associated health consequences.